2013
DOI: 10.1246/cl.130019
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Dependence of the Proton Transport and Oriented Structure in Oligo[(1,2-propanediamine)-alt-(oxalic acid)] Thin Films

Abstract: Three oligo[(1,2-propanediamine)-alt-(oxalic acid)] thin films were prepared on SiO 2 , R-plane sapphire, and MgO(100) substrates, and their proton conductivities were investigated. Conductivity depended on the substrate and varied from 4 © 10 ¹3 to 1 © 10 ¹4 S cm ¹1 under the same conditions (80% relative humidity and 298 K). The thin films between the Rplane (1102) sapphire and MgO(100) substrates showed different molecular oriented structures. The thin film on the sapphire substrate, which shows higher prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Recently, we have found the substrate dependence between MgO and sapphire of the proton transport in the thin film and this was originated from the oriented structure at the interface. 46 These results suggest to us a possible route to fabricate thin films of different proton transport properties by substrate selection. However, the preexponential factor (σ 0 ) in the Arrhenius eq 1 for the SiO 2 substrate is higher than that for the MgO substrate.…”
Section: Resultsmentioning
confidence: 82%
“…Recently, we have found the substrate dependence between MgO and sapphire of the proton transport in the thin film and this was originated from the oriented structure at the interface. 46 These results suggest to us a possible route to fabricate thin films of different proton transport properties by substrate selection. However, the preexponential factor (σ 0 ) in the Arrhenius eq 1 for the SiO 2 substrate is higher than that for the MgO substrate.…”
Section: Resultsmentioning
confidence: 82%
“…Results showed that proton conductivity is changed by molecular orientation of the polymer according to an interaction between the substrate and the polymer interface [21,22]. In 2008, the first report was made of a study in which the proton conductivity of oligo[(1,2-propanediamine)-alt-(oxalic acid)] thin films was improved by the molecular orientation [23][24][25]. As the oriented structure of other research groups, Tamura and Kawakami presented composite membranes containing uniaxially aligned sulfonated polyimide nanofibers by an electrospinning process (Figure 1(f)) [26].…”
Section: Introductionmentioning
confidence: 99%
“…In combination with X-ray scattering technique, it is useful to discuss the structure of crystalline and amorphous parts in other materials [43,44,47,48,[52][53][54]. It also makes it possible to discuss the substrate dependence in greater detail [25,36,37] or casting solvent dependence [43,54] of the interfacial structure.…”
Section: Introductionmentioning
confidence: 99%
“…In recent polymer research fields, taking advantage of the interface extends the molecular design such as the oriented structure and organized structure for the highly proton conductive materials. In this Feature Article, I proposed the concept of molecular orientation to improve proton conductivity for various proton conductive polymers using the interface of substrate surfaces. The interface can modify the degrees of freedom for polymer structures through interaction with functional groups, wettability, and the surface charge between the substrate surface and polymers. Some proton conductive polymers exhibit an oriented structure by the fabrication of thin films.…”
Section: Introductionmentioning
confidence: 99%
“…Copyright 2009 Elsevier. Plots c–e were adapted with permission from ref . Copyright 2013 The Chemical Society of Japan.…”
Section: Introductionmentioning
confidence: 99%